Medico-social aspects of the prevention of noncommunicable diseases - T.V. Peresypkina (Zaslavsky O.Yu., 2017)
Background. The noncommunicable disease (NCDs) are very common among population around the world. They are the main cause of preventable mortality, cause temporary and permanent disability. NCDs are the major reason for attending for medical care and lead to economic losses. The implementations of preventive strategy, increasing the role of preventive measures are general tasks for all health care system. The analysis of trends of preventive measure for NCD nowadays is the aim of this research. Materials and methods. The study included the result of analysis of science publication and WHO database about NCD and preventive measure used as well as the results of the analysis of data of the Center for Statistics in Medicine of MoH of Ukraine. Results. Diabetes, cardiovascular diseases, cancer, chronic respiratory diseases are the major NCDs. The base factors which lead to NCD are behavioral risk factors, namely tobacco use, unhealthy diet, physical inactivity, and alcohol abuse. The WHO prepared a lot of documents, among which the most significant are the strategies on noncommunicable diseases prevention, convention against smoking, strategy on diet and physical activity, global strategy on reducing alcohol abusing and so on. Nowadays the world population follows Global Action Plan for Prevention of Noncommunicable Diseases for 2013-2020. The documents emphasize the importance of state support, the use of scientific potential and intersectoral interaction to effectively combat noncommunicable diseases. The major of scientific direction are NCD monitoring, detection of the determinant of NCD development and making strategy for usage it in conditions of limited resources. The role of Digital marketing today increases that leads to the acquisition and consolidation of the habits and behavior of modern youth. Internet marketing is very effective to form unhealthy food behavior in children and adolescents that requires adequate and urgent actions. The project of NCD prevention and improving health status in Ukraine began in Kharkiv region. Conclusions. The strategic direction of health protection in Ukraine (for the period up to 2025) is to increase the duration of healthy (active) life by preventing non-infectious pathology among adolescents and young people. Priority measures for the prevention of noncommunicable diseases of the younger generation should be monitoring and evaluating existing problems, a clear vision of the ultimate goals, a large number of stakeholders and support for evidence-based research on the prevention of noncommunicable diseases.